Tanggap Tanaman Tomat (Lycopersicum esculentum. Mill) Terhadap Pemberian Kombinasi Pupuk Organik dan Pupuk Anorganik (Tomato (Lycopersicum esculentum. Mill) response to organic and inorganic fertilizers combination) - Elis Kartika; Zul Fahri Gani; Diki Kurniawan (Bioplantae, 2013)
Low soil fertility is one of the main factors responsible for low productivity of tomato in Jambi Province. Soil fertility can be presumably enhanced by organic and inorganic fertilizers application. The objective of this experiment was to investigate the effect of different organic and inorganic fertilizers combination  on  plant growth and yield. One of the liquid organic fertilizer  that commonly  used     is Hantu organic fertilizer.  The research design was Randomized Block design, the treatment is organic fertilizer Hantu combined with various doses of inorganic fertilizers, 2000 ppm of organic fertilizer +  0.0 % of inorganic fertilizers, 2000 ppm of organic fertilizer + 25.0 % of inorganic fertilizers, 2000 ppm of organic fertilizer + 50.0 % of inorganic fertilizers, 2000 ppm of organic fertilizer + 75.0 % of inorganic fertilizers, 2000 ppm of organic fertilizer + 100% of inorganic fertilizers and 0.0 ppm of organic fertilizers +100% of inorganic fertilizers. Variables measured were plant height, plant dry weight, number of flowers per plant, number of fruits per plant, percentage of flowers become fruit, and fruit weight per plant. The results showed that application of 2000 ppm of organic fertilizer and 75.0 % of inorganic fertilizers showed the best growth and yield of tomato plants.      Keywords: Hantu organic fertilizer, inorganic fertilizer, tomato